Case report: Clinical and molecular characterization of two siblings affected by Brody myopathy - Velardo, Daniele; Antognozzi, Sara; Rimoldi, Martina; Pagliarani, Serena; Cogiamanian, Filippo; Barbieri, Sergio; Corti, Stefania; Comi, Giacomo Pietro; Ronchi, Dario (Frontiers in Neurology, 2023)
Exercise-induced muscle stiffness is the hallmark of Brody disease, an autosomal recessive myopathy due to biallelic pathogenic variants in ATP2A1, encoding the sarcoplasmic/endoplasmic reticulum Ca2+ ATPase SERCA1. About 40 patients have been reported so far. Our knowledge about the natural history of this disorder, genotype–phenotype correlations and the effect of symptomatic treatment is partial. This results in incomplete recognition and underdiagnosis of the disease. Here, we report the clinical, instrumental, and molecular features of two siblings presenting childhood-onset exercise-induced muscle stiffness without pain. Both the probands display difficulty in climbing stairs and running, frequent falls, delayed muscle relaxation after exertion. Cold temperatures worsen these symptoms. No myotonic discharges were observed at electromyography. Whole Exome Sequencing analysis in the probands revealed the presence of two ATP2A1 variants: the previously reported frameshift microdeletion c.2464delC and the likely pathogenic novel splice-site variant c.324 + 1G > A, whose detrimental effect was demonstrated in ATP2A1 transcript analysis. The bi-allelic inheritance was verified by Sanger sequencing in the unaffected parents. This study expands the molecular defects associated with Brody myopathy.